A mouse model of microglia-specific ablation in the embryonic central nervous system. (December 2021) - Li, Chenmin; Konishi, Hiroyuki; Nishiwaki, Kimitoshi; Sato, Katsuaki; Miyata, Takaki; Kiyama, Hiroshi
Highlights: A technique for microglia-specific ablation in the embryonic CNS was established. Siglec-H is specifically expressed by microglia in the embryonic CNS. Diphtheria toxin was injected into the amniotic fluid of Siglech dtr embryos. Microglia were depleted for several days throughout the CNS. Other CNS macrophage species were not ablated, indicating microglial specificity. Abstract: Microglia, which migrate into the central nervous system (CNS) during the early embryonic stages, are considered to play various roles in CNS development. However, their embryonic roles are largely unknown, partly due to the lack of an effective microglial ablation system in the embryo. Here, we show a microglial ablation model by injecting diphtheria toxin (DT) into the amniotic fluid of Siglech dtr mice, in which the gene encoding DT receptor is knocked into the microglia-specific gene locus Siglech . We revealed that embryonic microglia were depleted for several days throughout the CNS, including some regions where microglia transiently accumulated, at any embryonic time point from embryonic day 10.5, when microglia colonize the CNS. This ablation system was specific for microglia because CNS-associated macrophages, which are a distinct population from microglia that reside in the CNS interfaces such as meninges, were unaffected. Therefore, this microglial ablation system is highly effective for studying the embryonic functions of microglia.